2017
DOI: 10.3892/ol.2017.6587
|View full text |Cite
|
Sign up to set email alerts
|

Notch 1 is a valuable therapeutic target against cell survival and proliferation in clear cell renal cell carcinoma

Abstract: Notch 1 is a key component of the Notch pathway, which performs a crucial role in clear cell renal cell carcinoma (CCRCC) development. The present study aimed to investigate whether Notch 1 could serve as a potential target for CCRCC treatment. Firstly, an association analysis was performed using 52 CCRCC cases and 30 normal controls. The results indicated that Notch 1 protein expression in renal tissues was closely associated with the incidence of CCRCC. In addition, higher Notch 1 expression in CCRCC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…In terms of the individual genes, NOTCH1 expression was positively correlated with clear cell renal cell carcinoma (CCRCC) carcinogenesis and progression. Indeed, Zhuang Z. and colleagues reported that NOTCH1 protein expression was exhibited in patients with higher TNM stage or Fuhrman grade or larger tumor size [ 64 ]. Moreover, NOTCH1 and JAG1 expression were significantly elevated in localized and metastatic CCRCC tumors [ 65 , 66 ], and they were also linked to reduced overall and disease-free survival [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the individual genes, NOTCH1 expression was positively correlated with clear cell renal cell carcinoma (CCRCC) carcinogenesis and progression. Indeed, Zhuang Z. and colleagues reported that NOTCH1 protein expression was exhibited in patients with higher TNM stage or Fuhrman grade or larger tumor size [ 64 ]. Moreover, NOTCH1 and JAG1 expression were significantly elevated in localized and metastatic CCRCC tumors [ 65 , 66 ], and they were also linked to reduced overall and disease-free survival [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific inhibition of Notch1 in renal carcinoma cells reduced the level of B-cell lymphoma/leukemia-2 (BC1-2) proteib and increased apoptosis. Meanwhile, the phosphorylation of phosphatidylinositol-3kinase (P13K)/protein kinase B (Akt), which is involved in promoting cell growth and proliferation, decreased [ 49 ], suggesting that Notch1 simultaneously regulates the proliferation and apoptosis of tumor cells and inhibits Notch1 signaling, which may be a new therapeutic target. Von Hippe1 is known to cause protein inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH1 expression is associated with poor survival as well as advanced grade or TNM stage in hepatocellular carcinoma (HCC) and colorectal cancer [ 10 ]. In clear cell RCC, NOTCH1 expression is associated with advanced TNM stage and higher Fuhrman grade [ 11 ]. ARID1A loss—correlated with microsatellite instability and increased mutation burden across cancer types [ 12 ]—has shown favorable prognostic impact—is known to be associated with peritumoral lymphoid aggregates/tumor-infiltrating lymphocytes—in esophageal adenocarcinoma, suggesting the impact of neoantigen-induced immunogenicity on survival [ 13 ].…”
Section: Discussionmentioning
confidence: 99%